George Sutherland papers - Sutherland, George, 1862-1942.
Correspondence, memoranda, diaries, speeches, notes, legal files, biographical material, scrapbooks, printed matter, and other papers relating primarily to Sutherland's service as U.S. congressman and senator from Utah and U.S. Supreme Court associate justice. Subjects include his affiliation with the American Bar Association, presidential campaign of 1920, appointment of Sutherland to the bench in 1922, Supreme Court packing fight of 1937, U.S. Senate Committee on the Judiciary, and Utah politics. Correspondents include William Edgar Borah, Louis Dembitz Brandeis, Tom Connally, Carter Glass, Warren G. Harding, Charles Evans Hughes, Henry Cabot Lodge, Theodore Roosevelt, Elihu Root, William H. Taft, and John Sharp Williams.
Lawyer, U.S. senator from Utah, and associate justice of the Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Borah, William Edgar, -- 1865-1940 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Connally, Tom, -- 1877-1963 -- Correspondence; Glass, Carter, -- 1858-1946 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Williams, John Sharp, -- 1854-1932 -- Correspondence; United States. -- Congress. -- Senate. -- Committee on the Judiciary; United States. -- Supreme Court; American Bar Association; Constitutional law -- United States; Elections -- United States -- 1920.; Judges -- Selection and appointment -- United States; Law -- United States; United States -- Politics and government -- 1901-1953.; Utah -- Politics and government; Jurists; Lawyers; Senators, U.S. Congress -- Utah